Direct synthesis of dimethyl carbonate from CO2 and methanol over CeO2 catalysts of different morphologies - Unnikrishnan, P.; Darbha, Srinivas (Journal of Chemical Sciences, 2016)
The direct synthesis of dimethyl carbonate (DMC) from carbon dioxide (CO2) and methanol is an attractive approach towards conversion of the greenhouse gas - CO2 into value-added chemicals and fuels. Ceria (CeO2) catalyzes this reaction. But the conversion efficiency of CeO2 is enhanced when the byproduct water in the reaction medium is separated by employing trapping agents like 2-cyanopyridine (2-CP). In this work, the influence of morphology of CeO2 on the direct synthesis of DMC in presence of 2-CP is reported. CeO2 catalysts of cube, rod, spindle and irregular morphology (Ce - C, Ce - R, Ce - S and Ce - N, respectively) were prepared, characterized and studied as catalysts in the said reaction conducted in a batch mode. Among all, Ce - S shows superior catalytic performance with nearly 100 mol% of DMC selectivity. Catalytic activity correlates with the concentration of acid and base sites of medium strength as well as defect sites. Ce - S has an optimum number of these active sites and thereby shows superior catalytic performance.
Keywords: acid-base catalysis; ceria; CO2 utilization; Dimethyl carbonate; influence of morphology